The Moderation Effect of Bank Operational Efficiency on Digital Banking Health and Stock Performance - Saparila Worokinasih; Darma Aji Ramadhani; Rani Arifah Normawati (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2026)
This study aims to examine the influence of bank soundness on stock performance among digital banks in Indonesia. The RGEC framework, which includes Risk Profile, Good Corporate Governance (GCG), Earnings, and Capital, is used to measure how sound a bank is. The study also investigates whether operational efficiency, represented by the BOPO ratio, moderates the relationship between each RGEC component and stock performance. A quantitative approach was employed using secondary data from digital banks listed on the Indonesia Stock Exchange during 2021–2022. After applying the selection criteria, 64 financial statement observations were analyzed using SEM-PLS. The findings demonstrate that solely the GCG component, assessed via management ownership, substantially influences stock performance as indicated by the price-to-earnings ratio (PER). Capital exhibits an unexpected negative influence, while other variables are statistically insignificant. These results expand the literature on bank soundness and stock market performance, particularly within the underexplored context of Indonesia’s digital banking sector.